LIVER ENZYME ALTERATIONS AFTER LAPAROSCOPIC CHOLECYSTECTOMY IN A TERTIARY CARE CENTER - Amar Varshney,; KAWATRA, VIPIN; KP, MISHRA; DWIVEDI, SURJEET K (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Cholelithiasis is a prevalent global health concern, with laparoscopic cholecystectomy (LC) emerging as the preferred surgical intervention. While LC offers an advantage such as shorter hospital stays, it poses potential risks, including cardiovascular impediments because of hemodynamic and ventilatory changes. The current research study was done to assess the impact of LC on hematological parameters, comparing pre-operative and post-operative levels. Methods: The study comprised 51 subjects undertaking LC, and preoperative and postoperative blood samples were analyzed for various hematological parameters. Parameters investigated included hemoglobin (Hb), mean corpuscular volume, mean corpuscular Hb, mean corpuscular Hb concentration, hematocrit, platelet count, mean platelet volume (MPV), and liver function tests such as alanine transaminase and alkaline phosphatase. Results: Preliminary findings demonstrated significant alterations in hematological parameters post-LC. Changes in MPV, leukocytes, neutrophils, neutrophil–lymphocyte ratio, platelet–lymphocyte ratio, and coagulation factors were observed. Moreover, there was a notable proliferation in thromboembolic measures connected with pneumoperitoneum pressure and surgery duration. Conclusion: LC induces substantial changes in hematological parameters, potentially contributing to postoperative complications. Understanding these alterations is crucial for implementing appropriate pre-, peri-, and post-operative measures to minimize morbidity, mortality, and overall health-care costs. Further investigations are required in interpreting the principal mechanisms and refine strategies for optimizing patient outcomes in LC.